Mitigation and risk factor analysis of android applications. (October 2018) - Sharma, Kavita; Gupta, B.B.
Abstract: Today, researchers face numerous challenges when attempting to identify malicious apps in the android market. Android apps require permissions to access the functionality of the mobile device. Moreover, these permissions can be used to know the app's behaviour. In this paper, we present a novel approach (called RNPDroid) for risk mitigation using the analysis of permissions. To evaluate the proposed approach, the M0Droid dataset is used, which consists of 400 Android app samples. All permissions of the obtained samples are analysed through reverse engineering, and total 165 permissions are attained. The computed value of F (517.3) is much higher than the tabulated value of F (2.61) at a 5% level of significance. The analysis of variance (ANOVA) states that one of the risk factors is significantly different from others. Moreover, the t -test is used to show the significant difference between medium and low risk.